The Effect of Advertising Content (Entertainment, Irritation, Informativeness) on Consumer Response and Purchase Intention in Tokopedia WhatsApp Broadcast Advertisements - Nabila, Alifia Salma; Mujanah, Siti; Fianto, Achmmad Yanu Alif (Universitas KH. Abdul Chalim Mojokerto, 2026)
The advancement of the digital era at this time many ways to promote products or services, including Tokopedia promoting through the WhatsApp broadcast social media platform. Through WhatsApp broadcast as a marketing medium with effective and relevant advertising content, it will have an impact on consumer purchasing intentions. The purpose of this study is to examine the impact of advertising content (entertainment, irritation, informativeness) on advertising value, attitude towards advertising, and flow experience, as well as its influence on purchase intention. This study was conducted using a quantitative approach through an online survey distributed via Google Form to respondents who had at least seen Tokopedia advertisements on WhatsApp broadcasts. There were a total of 197 respondents. Data analysis in this study used Smart PLS 3.0. The results showed that entertainment and informativeness had a positive and significant effect, while irritation had a negative and significant effect on advertising value, attitude towards advertisement, and flow experience. Furthermore, it was proven that advertising value and flow experience had a significant positive effect on purchase intention, while attitude towards advertisement did not have a significant effect on purchase intention.